2012
DOI: 10.1186/1471-230x-12-75
|View full text |Cite
|
Sign up to set email alerts
|

Back-to-Back Comparison of Auto-Fluorescence Imaging (AFI) Versus High Resolution White Light Colonoscopy for Adenoma Detection

Abstract: BackgroundSome patients under close colonoscopic surveillance still develop colorectal cancer, thus suggesting the overlook of colorectal adenoma by endoscopists. AFI detects colorectal adenoma as a clear magenta, therefore the efficacy of AFI is expected to improve the detection ability of colorectal adenoma. The aim of this study is to determine the efficacy of AFI in detecting colorectal adenoma.MethodsThis study enrolled 88 patients who underwent colonoscopy at Asahikawa Medical University and Kushiro Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 41 publications
(45 reference statements)
0
32
1
Order By: Relevance
“…Two consecutive same-day colonoscopies were performed in a total of 183 patients and the overall miss rate for adenomas was 24% showing superiority in adenoma detection by back-to-back colonoscopy. This technique is now often used in studies comparing new endoscopic devices for adenoma detection improvement to overcome the lack of study blinding [59,60,61,62]. In another large multicenter study conducted in 2008 by Heresbach et al [63] with same-day back-to-back video colonoscopy done by 2 different operators in a randomized order and blinded to the other examination, 20% of adenomas that were missed at first colonoscopy could additionally be detected.…”
Section: Factors Influencing the Adrmentioning
confidence: 99%
“…Two consecutive same-day colonoscopies were performed in a total of 183 patients and the overall miss rate for adenomas was 24% showing superiority in adenoma detection by back-to-back colonoscopy. This technique is now often used in studies comparing new endoscopic devices for adenoma detection improvement to overcome the lack of study blinding [59,60,61,62]. In another large multicenter study conducted in 2008 by Heresbach et al [63] with same-day back-to-back video colonoscopy done by 2 different operators in a randomized order and blinded to the other examination, 20% of adenomas that were missed at first colonoscopy could additionally be detected.…”
Section: Factors Influencing the Adrmentioning
confidence: 99%
“…42, 43 We previously reported the usefulness of AFI for the detection of colon polyps compared with conventional high-definition white light, a prospective study based on a single center. 44 In this pilot study, the miss rate for all polyps with AFI (30%) was significantly less than that with conventional high-definition white light (49%) (P = 0.01).…”
Section: Autofluorescence Imagingmentioning
confidence: 99%
“…We compared the rates at which experienced and less-experienced endoscopists detected adenomas using AFI and conventional high-resolution endoscopy (HRE). Among less-experienced endoscopists (but not experienced endoscopists), AFI was found to dramatically increase the detection rate (30.3 %) and reduce the miss rate (0 %) of colorectal adenoma in comparison to HRE (7.7, 50.0 %) [20]. McCallum et al compared the detection rates in 54 adenomatous polyps, including 32 tubular polyps, four villous polyps, and 18 tubulovillous polyps (median size, 4 mm) using AFI and WLE.…”
Section: Detectionmentioning
confidence: 99%
“…Some studies have proposed the efficacy of AFI for detecting colorectal neoplasms [10,[20][21][22]. Matsuda et al reported a study in which a single experienced endoscopist conducted back-to-back colonoscopies of the right-sided colon using AFI and WLE.…”
Section: Detectionmentioning
confidence: 99%